Overcoming Maternal and Child Health Problems in Rw 16 Citatah Village, Cipatat District, West - MG Sianipar, Imelda; Triana, Hani; Purnasari, Henni (CV Media Inti Teknologi, 2024)
Based on the analysis of the situation from the initial survey data of community service activities, several health problems were obtained in RW 16, it can be concluded that there are 3 maternal and child health problems that are priorities for the community service team to overcome, namely: The prevalence of stunting in children under five years old, low coverage of immunization in children, and nutritional problems in pregnant women. The purpose of this service is to solve maternal and child health problems by providing health education to the community. This service activity employs the extension approach as its methodology. Data collection using questionnaire sheets that become material for evaluation. The outcomes of this service include the assessment of counseling participants' comprehension by oral questioning at the beginning and conclusion of the session. The community seemed enthusiastic about providing responses and answers and was actively involved during the counseling process. So it can be concluded that there is a social change in the form of changes in the way people think about health, especially maternal and child health, tracking the development and growth of children, early detection of diseases, and many other benefits that cause changes in the way people view health.